Tandem Nanostructures: A Prospective Platform for Photoelectrochemical Water Splitting - Liu, Jun; Zhao, Huaping; Wang, Zhijie; Hannappel, Thomas; Kramm, Ulrike I.; Etzold, Bastian J.M.; Lei, Yong (Solar RRL, 2022)
A platform for efficient photoelectrochemical (PEC) water splitting must fulfil different requirements: the absorption of the solar spectrum should be maximized in use for charge carrier generation. To avoid recombination, fast separation of charge carriers is required and the energetic positions of the band structure(s) must be optimized with respect to the water splitting reactions. In these respects, constructing tandem nanostructures with rationally designed nanostructured units offers a potential opportunity to break the performance bottleneck imposed by the unitary nanostructure. So far, quite a few tandem nanostructures have been designed, fabricated, and employed to improve the efficiency of PEC water splitting, and significant achievements have been realized. This review focuses on the current advances in tandem nanostructures for PEC water splitting. Firstly, the state of the art for tandem nanostructures applied in PEC water splitting is summarized. Secondly, the advances in this field and advantages arising of employing tandem nanostructures for PEC water splitting are outlined. Subsequently, different types of tandem nanostructures are reviewed, including core-shell tandem nanostructured photoelectrode, the two-photoelectrode tandem cell, and the tandem nanostructures of plasmon related devices for PEC water splitting. Based on this, the future perspective of this field is proposed.
CRIS-Team Scopus Importer:2023-08-15
Keywords: integrated advantages; photoelectrochemical water splitting; tandem nanostructures